(untitled) (Journal of history, 2021)
The article deals with the problems of traditional Kazakh society. The analysis of its ideological con- tent, socio-political structure, national values is shown. The role and place of formation of values, which are the main historical thinking, national culture of a traditional society, are defined. The problem of a comprehensive study of the structure of a traditional society was determined by traditional moderniza- tion. The idea of restoring the national ideology, spiritual sources, which is the cornerstone of history and culture, has been defined. It has been made a historical analysis of research in this direction. The historical conditions, economic and cultural prerequisites for the transformation of traditional Kazakh society are considered. Socio-economic changes contribute to the renewal of spiritual culture, its ideological rearmament. The worldview basis of this process was education. It is shown that in the educational teachings both ele- ments of the experience of the ideological and theoretical development of mankind and peculiar features of national self-consciousness were accumulated. Кеу words: traditional Kazakh society, transformation, patriarchal-feudal society, formation cam- paign, civilization, spiritual culture, Kazakh enlightenment.